Hair-Pulling Does Not Necessarily Serve an Emotion Regulation Function in Adults With Trichotillomania - Lochner, Christine; Demetriou, Salome; Kidd, Martin; Coetzee, Bronwynè; Stein, Dan J. (Frontiers in Psychology, 2021)
Background: Trichotillomania (TTM) has been associated with childhood trauma and perceived stress. While it has been hypothesized that hair-pulling regulate negative emotions, the relationship between childhood trauma, perceived stress, emotion regulation, and hair-pulling has not been well-studied. Methods: Fifty-six adults with TTM and 31 healthy controls completed the Childhood Trauma Questionnaire (CTQ), Perceived Stress Scale (PSS), and Difficulties in Emotion Regulation Scale (DERS). Hair-pulling severity was measured with the Massachusetts General Hospital-Hair Pulling Scale. CTQ, PSS, and DERS total scores were compared across groups using ANCOVA and the correlation between hair-pulling severity and emotion dysregulation was determined. Regression analyses were used to estimate the association of CTQ and PSS totals with DERS, and to determine whether associations between predictors and dependent variable (DERS) differed across groups. Results: TTM patients reported higher rates of childhood trauma (p <= 0.01), perceived stress (p = 0.03), and emotion dysregulation (p <= 0.01). There was no association between emotion dysregulation and pulling severity (r = −0.02, p = 0.89). Perceived stress was associated with emotion dysregulation in both groups (p < 0.01), and no association between childhood trauma and emotion dysregulation in either group. Perceived stress was the only significant predictor of emotion dysregulation in both groups (F = 28.29, p < 0.01). Conclusion: The association between perceived stress and emotion dysregulation is not specific to TTM, and there is no association between emotion dysregulation and hair-pulling severity, suggesting that key factors other than emotion dysregulation contribute to hair-pulling. Alternative explanatory models are needed.